1981
DOI: 10.1029/jb086ib01p00345
|View full text |Cite
|
Sign up to set email alerts
|

Tectonics and seismicity of the Toktogul Reservoir Region, Kirgizia, USSR

Abstract: The 214 m high Toktogul Dam will impound a 19.5‐km3 reservoir on the Naryn River in central Kirgizia. The reservoir lies along the Talas‐Fergana fault, a major tectonic feature of central Asia. The nature of Cenozoic movements along the fault is in debate; however, there is considerable evidence of present‐day right‐lateral movement. The region is one of moderate to high seismicity. A magnitude 7.6 earthquake occurred in 1946, approximately 65 km from the dam, near the intersection of the Talas‐Fergana fault a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…The recent deformation along this fault has been studied by several scientists over the past few decades, with a number of works appearing in English (Simpson et al, 1981;Burtman et al, 1987Burtman et al, , 1996Makarov 1989;Trifonov et al, 1990Trifonov et al, , 1992Korzhenkov et al, 2013). There is clear evidence of surface faulting events with river channel offsets (in the order of 25-100 m), along tens of km long faults, characteristics that are typical of large magnitude earthquakes (McCalpin, 1996).…”
Section: Tectonic and Geological Settingmentioning
confidence: 96%
See 2 more Smart Citations
“…The recent deformation along this fault has been studied by several scientists over the past few decades, with a number of works appearing in English (Simpson et al, 1981;Burtman et al, 1987Burtman et al, , 1996Makarov 1989;Trifonov et al, 1990Trifonov et al, , 1992Korzhenkov et al, 2013). There is clear evidence of surface faulting events with river channel offsets (in the order of 25-100 m), along tens of km long faults, characteristics that are typical of large magnitude earthquakes (McCalpin, 1996).…”
Section: Tectonic and Geological Settingmentioning
confidence: 96%
“…However, although all authors agree on significant Holocene offsets along the TFF (review in Simpson et al, 1981), only a couple of studies have been published, in Russian, on the distribution of landslides along this fault (Korjenkov, 1997;Strom, 2009), despite recognition that large active faults in mountain settings may be associated with both shallow and deep-seated slope failures. Several researchers infer a generic relationship between active faults and slope failures (e.g.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…One of the major historic earthquakes, which occurred in 1946 with an Mw = 7.3 is located in the Chatkal region. Simpson et al (1981) suggested that this earthquake was associated with the complex zone at the oblique intersection of the Talas-Fergana fault and Chatkal range. (2) The Alai region with the Alai Valley (see Figure 1; SW Tien Shan), the Alai range north of the Alai Valley, and the Trans Alai Range south of the Alai Valley, which are all located to the south of the Fergana basin.…”
Section: Tectonic Settingmentioning
confidence: 99%
“…In many parts of the Tien Shan, concentrated zones of seismicity can be related to edges of zones of Hercynian deformation, e.g., along the Gissar-Kokshal fault in the southern Tien Shan (Gubin, 1967) and along the Talas-Fergana and main Tien Shan faults in the northern Tien Shan (Simpson et al, 1980). Scattered exposures of Hercynian age continue in outcrops northwest of the southern Tien Shan but become increasingly covered by Neogene and Quaternary sands (Markovskii, 1975;Yanskin, 1966).…”
mentioning
confidence: 99%